PELECEHAN SEKSUAL DI INSTITUSI PENDIDIKAN: SEBUAH PERSPEKTIF KEBIJAKAN - Deding Ishak (GoAcademica Research dan Publishing, 2020)
Sexual harassment is identified as a major and hidden public health problem in most institutions/organizations. Sexual harassment is often a hidden problem because victims are usually reluctant to report their experiences. Using data based on interviews and surveys, this study explores the effects of gender, race/ethnicity, sexual orientation, age at enrollment, student status, and time spent at the institution on students' risk of being victims of sexual harassment by peers and faculty/staff, as well as the extent of victimization of students who experience harassment. Then traditional undergraduate students, college students, and gender and sexual minority students were found to be at increased risk of harassment. Being female increases the chances of being sexually harassed by lecturers/staff and peers. Students who have racial minorities reported less sexual harassment, but would experience high pressure from the perpetrators and the surrounding community if they did report. This research is expected to find a way to create policies on cases of violence and sexual harassment in educational institutions.